1987
DOI: 10.1039/c39870001805
|View full text |Cite
|
Sign up to set email alerts
|

Living polymerization of substituted acetylenes by MoCl5- and MoOCl4-based catalysts

Abstract: New catalyst systems composed of MoCl5 (or MoOC14), Bw4Sn, and ethanol (molar ratio 1 : 1 : 0.5) effect living polymerisations of 1 -chloro-oct-1 -yne and o-(trimethylsilyl)phenylethyne, which are the first examples of living polymerisation of acetylenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 1 publication
2
18
0
Order By: Relevance
“…The Mw/Mn ratio for [Rh(NBD)Cl] 2 -TEA (1: 100) was 1.68 and that for the Rh complex alone was more than 3.0. This suggests the presence of long-lived propagation species in these polymerization systems, as reported by Masuda et al 5 in the case of chloroalkyne. This polymerization behaviour is somewhat different from ordinary living polymerization 5 between the increase of Mn and amount of monomer supplied or conversion of monomer consumed as can be seen in Figure 1 and The resultant species may be considered to produced an active center responsible for a propagation species in this polymerization system.…”
supporting
confidence: 53%
See 1 more Smart Citation
“…The Mw/Mn ratio for [Rh(NBD)Cl] 2 -TEA (1: 100) was 1.68 and that for the Rh complex alone was more than 3.0. This suggests the presence of long-lived propagation species in these polymerization systems, as reported by Masuda et al 5 in the case of chloroalkyne. This polymerization behaviour is somewhat different from ordinary living polymerization 5 between the increase of Mn and amount of monomer supplied or conversion of monomer consumed as can be seen in Figure 1 and The resultant species may be considered to produced an active center responsible for a propagation species in this polymerization system.…”
supporting
confidence: 53%
“…This suggests the presence of long-lived propagation species in these polymerization systems, as reported by Masuda et al 5 in the case of chloroalkyne. This polymerization behaviour is somewhat different from ordinary living polymerization 5 between the increase of Mn and amount of monomer supplied or conversion of monomer consumed as can be seen in Figure 1 and The resultant species may be considered to produced an active center responsible for a propagation species in this polymerization system. In fact, the dimer-monomer equilibrium of the Rh-catalyst in chloroform was verified by our preliminary study using 1 H I l06 NMR and it was shown that the degree of the dissociation changes with the concentration of TEA used.…”
supporting
confidence: 53%
“…2), to find suitable ill‐defined initiating systems for the effective polymerization of substituted acetylenes 14, 15, 18, 56. In terms of the synthesis of tailor‐made polyacetylenes, the year 1987 was a milestone, when research groups led by Masuda and Higashimura68 and Percec69 independently reported on the first living polymerizations of some alkynes. On the basis of the hypothesis that acetylene derivatives bearing sterically demanding substituents should suppress back‐biting and interchain reactions due to steric hindrance, Kunzler and Percec69, 70 claimed that TaCl 5 ( 5 ) and MoCl 5 ( 6 ) effect the living polymerization of 1‐trimethylsilyl‐1‐propyne in toluene at 80 °C and t ‐butylacetylene in toluene at 30 °C, respectively (Table 1).…”
Section: Transition‐metal Halide‐basedinitiatorsmentioning
confidence: 99%
“…47 The MoOCl 4 -n-Bu 4 Sn-EtOH (1:1:0.5) catalyst (Chart 3) induced living polymerization of 6b in toluene at 30 8C. 48,49 The M n of polymer increased progressively with repeated additions of monomer feed. The polydispersity ratio (M w /M n ) was maintained at about 1.15.…”
Section: Metathesis Mechanismmentioning
confidence: 99%